Characteristics of transfusion‐transmitted Babesia microti, American Red Cross 2010‐2017. Issue 9 (27th June 2019) - Tonnetti, Laura; Townsend, Rebecca L.; Dodd, Roger Y.; Stramer, Susan L.
Abstract : BACKGROUND: Babesia microti, a red blood cell (RBC) parasite transmitted naturally to vertebrate hosts by ixodid ticks, is endemic to the northeastern and upper midwestern United States, with the geographic range of infected ticks expanding. B. microti is a blood safety issue with >200 transfusion‐transmissions reported. METHODS: The American Red Cross's Hemovigilance program investigated hospital‐reported transfusion‐transmitted babesiosis (TTB) cases. Follow‐up samples from involved donors were tested for B. microti antibodies and parasite DNA, the latter by real‐time polymerase chain reaction (PCR). Test‐positive donors were permanently deferred from future donations. RESULTS: B. microti ‐positive donors were implicated in 77 of 143 suspect TTB cases investigated from 2010 through 2017. In four cases, two positive donors were identified for a total of 81 positive donors. In three cases, a RBC unit was split and components transfused multiple times to the same pediatric recipient. RBCs were the transmitting product in all cases. At follow‐up, all involved donors were antibody positive; 25 donors were also PCR positive. Positive donations were collected throughout the year, peaking in the summer. Most donors (78) were resident of, or traveled to (2), an endemic state. One donor resided in a non‐endemic state without relevant travel history. One fatality listed babesia as a contributing factor. No implicated donation was screened by an investigational protocol. CONCLUSIONS: Babesiosis remains a blood safety issue. Prior to FDA‐licensed screening test availability and final FDA Guidance, blood collectors in endemic states investigationally tested none, a portion, or all collections. Future expanded testing will reduce the frequency of TTB cases.